Analysis of Lecturers' Financial Literacy Levels Faculty of Teacher Training and Education Langlangbuana University - Herdhiana, Ria; Suherman, Fugiyar; Ilyas, Ilyas (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2023)
Financial literacy needs to be owned by every individual because decisions in managing finances must be financial literacy. Financial literacy is one of the basic needs for every individual to avoid financial problems. The purpose of this study is to describe the level of financial literacy of lecturers and aspects of financial literacy including aspects of basic financial knowledge, savings and savings, insurance, and investment. This research method is descriptive research based on a survey of research subjects. The subjects of this study were lecturers at the Teaching and Education Faculty of Langlangbuana University in 2022. The results of the study illustrate that the average financial literacy level of lecturers at the Teaching and Education Faculty, Langlangbuana University in 2022 is 76.21% and is included in the medium category, which means that they still have efforts are made to increase the understanding of lecturers' financial literacy in every aspect of financial literacy to be even better to reach the level of well literate.